Dosimetric analysis of rib interference of the CTV during interstitial brachytherapy of lung tumors - Yang, Bo; Sun, Xiaoyang; Pang, Haowen; Shi, Xiangxiang; Tang, Tao; Zhang, Guangpeng; Chen, Renjin; Zhang, Jing; Wu, Hong; Lin, Sheng; Wen, Qinglian; Han, Yunwei; et al. (Journal of Contemporary Brachytherapy, 2017)
Purpose : In interstitial brachytherapy for lung tumors, the placement and alignment of the source needles are influenced by the ribs, which can affect the dose distribution. This study evaluated the change in dose to the target by comparing the dose between the actual interstitial brachytherapy plan (AIBP, what is deliverable due to anatomic constraints), and the virtual interstitial brachytherapy plan (VIBP, pretreatment-modified dose distribution). Material and methods : AIBPs and VIBPs were designed for 20 lung tumors. The VIBP was designed with uniform spacing between needles, regardless of the presence of ribs. The prescription dose was 30 Gy. The percentage of normal ipsilateral lung volume that received a dose ≥ 5 Gy (V 5 ), conformity index (COIN), incremental dose percentage (IDP) to the target, and the dose covering 95% (D 95 ) of the clinical target volume (CTV) were calculated. Results : The V 5 of the VIBPs was significantly smaller than that of the AIBPs (p < 0.01). The mean COIN value was 0.41 ± 0.12 for the AIBPs, which was significantly smaller than the value 0.54 ± 0.12 for the VIBPs (p < 0.01). The D 95 of CTV in VIBP-adjusted was greater than that in AIBPs (p < 0.01). The mean IDP was 44% ± 40%. The D max of the ribs was 20.16 Gy ± 15.76 Gy in AIBPs, and 18.57 Gy ± 15.14 Gy in VIBPs, which was not significantly different (p > 0.05). Conclusions : The regular geometric alignment of needles is important for increasing the target dose and limiting the normal lung dose in interstitial brachytherapy for thoracic tumors. Thus, we recommend that radiation oncologists attempt to achieve the regular alignment of needles during implantation.